Techniques for Creating Quality Questions in Learning Evaluation - Arbeni, Wawan; Ramanda, Ramanda; Aulia, Muhammad Hanif; Arika, Weni; Padilah, Siti (Holistic Science, 2025)
Learning evaluation is an integral part of the educational process, serving to objectively and systematically measure the achievement of learning objectives. One of the main instruments used in learning evaluation is test questions. However, in educational practice, many questions are still written without regard to good writing principles, resulting in low-quality learning evaluation results. This article aims to examine in-depth techniques for creating quality questions, including the rules for writing multiple-choice, essay, and true-false questions, question analysis and revision techniques, the preparation of question outlines, and the concepts of validity and reliability of assessment instruments. This study uses a literature study method by analyzing various relevant literature in the field of educational evaluation. The results of the study indicate that the preparation of quality questions must be based on careful planning through the preparation of question outlines, the application of writing principles according to the question format, and supported by a continuous process of analysis and revision of questions. In addition, the application of the principles of validity and reliability is a key factor in producing accurate and consistent evaluation instruments. Thus, mastery of quality question creation techniques by educators is a crucial requirement for improving the quality of learning evaluation and the quality of the learning process as a whole.